2002
DOI: 10.1177/152660280200900514
|View full text |Cite
|
Sign up to set email alerts
|

Gadodiamide as an Alternative Contrast Agent during Angioplasty in Patients with Contraindications to Iodinated Media

Abstract: For patients with contraindications to iodinated materials, gadodiamide may be a suitable alternative for renal or peripheral DSA followed by angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In such patients, X‐ray DSA or CT angiography with iodinated contrast agents should be avoided as long as possible to prevent further damage to the kidneys. Some authors have reported using Gd instead of iodinated contrast during interventional procedures, and verified the safety of Gd (2, 18–20). However, the off‐label use of Gd is not universally recommended (21).…”
Section: Discussionmentioning
confidence: 89%
“…In such patients, X‐ray DSA or CT angiography with iodinated contrast agents should be avoided as long as possible to prevent further damage to the kidneys. Some authors have reported using Gd instead of iodinated contrast during interventional procedures, and verified the safety of Gd (2, 18–20). However, the off‐label use of Gd is not universally recommended (21).…”
Section: Discussionmentioning
confidence: 89%
“…Zeller et al examined the use of gadodiamide as the sole contrast agent in patients with iodinated contrast allergy for digital subtraction angiography and angioplasty with or without stent placement [27]. The volume of gadodiamide administered ranged from 60 to 200 mL (mean volume being 136 ± 46 mL).…”
Section: Resultsmentioning
confidence: 99%
“…13 Image quality during fluoroscopic studies, though inferior to iodinated contrast agents, is often adequate and successful peripheral and renal artery intervention using gadolinium or related agents has been reported. 5 Caridi et al 4 described renal artery angioplasty in 21 patients using digital subtraction angiography with CO 2 contrast. Six of the patients had allergic contraindications to standard agents, and all interventions were successful.…”
Section: Discussionmentioning
confidence: 99%
“…3 Methods to avoid or minimize contrast usage include adjunctive ultrasound imaging, gadolinium-based contrast, and digital subtraction angiography with CO 2 contrast. [4][5][6] We report a patient with a history of severe, recurrent allergic reactions to iodinated contrast administration and symptomatic central vein stenosis successfully treated with intravascular sonography (IVUS) and pressure gradientdirected percutaneous angioplasty and stenting. No radiographic contrast agent was used during the diagnostic procedure or endovascular intervention.…”
mentioning
confidence: 99%